2012
DOI: 10.1159/000335196
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Up-Regulation of TLR4 Causes Lipopolysaccharide-Induced Augmentation of Nasal Cytokine Release in Allergic Rhinitis

Abstract: Background: Allergic rhinitis is a systemic disorder, and it is clinically well recognized that it can be aggravated by infection. Activation of the innate immune system constitutes a critical element in the process. Toll-like receptors (TLRs) comprise a part of the innate immune system, and lipopolysaccharide (LPS)-induced activation of TLR4 represents bacterial-induced interactions in various model systems. The present study examines how TLR2 and TLR4 expression is affected by symptomatic allergic rhinitis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…In line with this, most recent data on the topic show no eosinophil‐activating capability of LPS 16,17,76 . Moreover, recent observations from our laboratory show that TLR4 in eosinophils is up‐regulated in patients with allergic rhinitis during the pollen season 80 …”
Section: Expression and Function Of Prrs In Human Eosinophilssupporting
confidence: 78%
See 1 more Smart Citation
“…In line with this, most recent data on the topic show no eosinophil‐activating capability of LPS 16,17,76 . Moreover, recent observations from our laboratory show that TLR4 in eosinophils is up‐regulated in patients with allergic rhinitis during the pollen season 80 …”
Section: Expression and Function Of Prrs In Human Eosinophilssupporting
confidence: 78%
“…16,17,76 Moreover, recent observations from our laboratory show that TLR4 in eosinophils is up-regulated in patients with allergic rhinitis during the pollen season. 80 While one study found no evidence for TLR5 mRNA in human eosinophils, 16 another has detected the TLR5 protein using flow cytometry and Western blot. 17 The latter also demonstrates that the TLR5 ligand flagellin is capable of inducing eosinophil activation in terms of chemokine and cytokine secretion (IL-1b, IL-6, IL-8, GRO-a), superoxide generation, prolongation of eosinophil survival and activation of the adhesion system (ICAM-1, CD18, ICAM-3, L-selectin) with a subsequent increase in CCL5-induced migration.…”
Section: Tlr Responsesmentioning
confidence: 99%
“…TLRs are pivotal actors in shaping the effective and healthy adaptive immunity with the development of immune deviation from the T-helper (Th) 2 to Th1 phenotype and maturation of T-reg cells [28,29]. Interestingly, the expression and function of TLRs [30,31,32,33,34] were demonstrated to be different in patients with asthma/AR as compared to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, nasal challenge with allergen followed by LPS augmented the release of IL-4, IL-5, IL-10, IL-13, IFN-c and TNF-a. For example, TLR-4 expression increased in leucocytes in nasal fluid, peripheral blood and BM during symptomatic allergic rhinitis.…”
Section: Discussionmentioning
confidence: 98%
“…For example, TLR-4 expression increased in leucocytes in nasal fluid, peripheral blood and BM during symptomatic allergic rhinitis. 15 Furthermore, nasal challenge with allergen followed by LPS augmented the release of IL-4, IL-5, IL-10, IL-13, IFN-c and TNF-a. 15 In contrast, allergen challenge does not affect TLR-9 expression on blood and sputum plasmacytoid dendritic cells, but impairs IFN-a production by these cells.…”
Section: Discussionmentioning
confidence: 98%